(3TQM ebOeI GdbdGFO aj JUMjM GdYbGFOs - (3YHO Gddg Hf eMeO Hf CHj GdbGSe GdRjOj GdYHSj GdfLQj, GdfLQj,J (B877 (3g` s ((3Ydi Hf MSf Hf CMeO GdYfGHi s)
(3ChdgG (B:s
(3cJGH GdJhMjO GdcJGH ai GdCUd eUOQ , hGdeQGO Hg gGgfG GdecJhH cGddaX HeYfi GdedahX s
(3BNQgG (B:s
(3hNha GdgLQI EdG GdEeGe adg Cf jfcQ Ydjg hjdReg ePgHg ceG JbOe Je GdcJGH Hef Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf HGdMeQIs
(3HChdgG JedjcGJ Ydi MhGTjgG JYdjbGJ s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdJGQjNs